Evaluation of strains derived from Escherichia coli W as hosts for the expression of penicillin G-acylase-encoding gene cloned on the recombinant plasmid pKA18 - Grafková, J; Sobotková, L; Kyslík, P (Folia microbiologica, 2002)
The potential for production of penicillin G-acylase (PGA), encoded by the chromosomal gene pgai, of four strains belonging to a genealogical line derived from the strain Escherichia coli W, was evaluated in a medium with and without the inducer phenylacetic acid (PA). These strains were used as hosts of the recombinant plasmid pKA18, in which the structural gene pgac isolated from the strain RE3, the best host strain of a line giving the highest production, was cloned. The presence of the inducer reduced the copy number of the plasmid in all recombinant strains. Only in recombinant strain RE3 (pKA18) the reduction of the gene dosage of pgac resulted also in the reduction of the amount of PGA synthesized by the cells. The reduced activity of the cells did not result from a segregation of plasmid-free clones. Also the growth rate was decreased by 20 and 40% in the host and recombinant strains, respectively. The host strain RE3 showing the highest production of PGA was also the best host of the recombinant plasmid in terms of the segregational stability and copy number (198 copies per chromosome). The recombinant strain RE3 (pKA18) also provided the highest production of PGA.
Keywords: regulace genové exprese u bakterií; Gene Expression Regulation, Bacterial; rekombinantní DNA; klonování DNA; penicilinamidasa; Plasmids; rekombinantní proteiny; Recombinant Proteins; DNA, Recombinant; plazmidy; Cloning, Molecular; Escherichia coli; Penicillin Amidase